Los Auditoria de Adriano y el Athenaeum de Roma - Lopez Garcia, Antonio (Premio Tesi di Dottorato, 2015)
In 2007, during the archaeological excavations for the construction of a metro station in Piazza Venezia in Rome, two auditoriums dating back to the first half of the 2nd century AD appeared; various archaeologists identified them as part of the Athenaeum founded by Hadrian, the first great Roman academic institution mentioned in the classical sources. This book is the result of an exhaustive analysis through topography, architecture and philology, in the attempt to reveal the functionality of the structures, which could have been part of the Athenaeum or perhaps of a judicial institution integrated into the set of courts of the Trajan's Forum.